Investigating the stresses and detailing on load bearing transfer wall with opening based on finite element method - Oon, Aaron Chern En (2023)
Reinforced concrete (RC) transfer walls are widely used in high-rise structures nowadays to transfer a massive amount of load to the supporting structure below. The presence of openings on large structuressuch as transfer walls would often be designed by engineers to meet the functional, architectural or mechanical requirements of the buildings. However, these openings are the source of weakness that affects the load transfer mechanism and the bearing capacity of the transfer wall. This study aimed to investigate the stress of the transfer wall with different opening configurations by finite element analysis and design the most efficient reinforcement detailing by adopting Eurocode 2. This research study utilised SCIA Engineer and ANSYS software to simulate the numerical analysis of the model where 2D and 3D analysis was carried out respectively by both software to evaluate the stress distribution pattern of the transfer wall. Findings revealed that the stress path was smoother for transfer wall with staggered openings compared to vertical aligned openings due to less stress flow disturbance. High stress was concentrated at the opening corners and supporting region of the transfer wall. Findings show that the design of steel reinforcement was provided according to the critical locations where were highly stressed. For instance, high density of steel reinforcement was provided especially at the supporting region, whereas diagonal reinforcement was provided at the opening’s corner to prevent cracking. The findings also show that the load path analysis of transfer walls can be well-presented in stress contour form by using numerical modelling through 2D and 3D finite element methods. However, the difference in stress value was huge due to the difference in analysis approach in terms of assumption and simplification, mesh density, the element type as well as the boundary conditions. The findings proved that 3D analysis provides more accurate results when dealing with geometrically complex structures such as the transfer wall with openings. Lastly, it was recommended that further study to be done for the finite element analysis method in terms of boundary conditions and mesh settings to improve the reliability and accuracy of the analysis results.